2015
DOI: 10.1089/chi.2014.0092
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes following the MEND 7–13 Child Weight Management Program

Abstract: Background: In the current study we report outcomes 2.4 years from baseline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Weight regain is often reported after overweight and obesity treatment [14,28]. In this study, the mean BMI SDS declined throughout 1.5 years of treatment in boys.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Weight regain is often reported after overweight and obesity treatment [14,28]. In this study, the mean BMI SDS declined throughout 1.5 years of treatment in boys.…”
Section: Discussionmentioning
confidence: 49%
“…Community-based treatment options have the advantages of being situated in the families’ local area and being accessible by self-referral, and thus may help improve treatment availability and accessibility [8,9]. Nonetheless, few overweight and obesity treatment programs have been evaluated in community healthcare settings, the results are mixed, and the long-term treatment effects are unclear [814]. In the United Kingdom, a nine-week community-based obesity treatment of 116 children aged 8−12 years resulted in a 0.30 reduction in body mass index (BMI) standard deviation score (SDS) (p<0.001), but at a 2.4-year follow-up after the MEND program, BMI SDS was not lower than at entry [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, publication bias is unlikely. The change in self‐esteem was maintained at follow‐up of up to 2.4 years from baseline in 17 studies (Figure B, 0.35 [0.05] P < .001, I 2 79%). Publication bias is unlikely (funnel plot symmetry, fail‐safe N = 1029 studies).…”
Section: Resultsmentioning
confidence: 95%
“…The change in body image between pre‐intervention and postintervention was reported in 27 studies, between pre‐intervention and follow‐up in three studies, and 13 studies reported data at all three time points. Of the 40 studies reporting body image pre‐intervention and postintervention ranging in duration from 2 weeks to 24 months, body image was reported to be significantly improved compared with baseline in 22 studies, not significantly changed in 10 studies, five studies did not state whether or not the change was significant and three studies reported a significant improvement in one body image measure and no change in another.…”
Section: Resultsmentioning
confidence: 99%